Nosocomial Infections Pathogens Isolated from Hospital Personnel, Hospital Environment and Devices - Reza Akbari; Mehdi Fattahi Bafghi; Hossain Fazeli (Journal of Medical Bacteriology, 2018)
Background:    Nosocomial infections has always been a major problem for health care and lead to increases in morbidity and mortality in hospitalized patients. The aim of this study was to determine the contamination of personnel and hospital environment and device with nosocomial infections pathogens.